Pengaruh Penambahan Bubuk Cascara Arabika Kintamani terhadap SifatKimia dan Organoleptik Cascara crispy: The Effect of Adding Kintamani Arabica Cascara Powder on the Chemical and Organoleptic Properties of Cascara Crispy - Alizza Zahira Prameswari; Sayi Hatiningsih; Jason Patrick Kenardi; Ni Made Mutia Pradnyawangi; Ida Ayu Agung Prapita Hermayuli; I Putu Agus Artawan (Jurnal Teknologi dan Mutu Pangan, 2026)
Cascara crispy is a thin, crispy biscuit product made from cascara that has the potential to be developed as a functional food derived from agricultural waste, with nutritional value due to its fiber and antioxidant activity. This study aims to determine the optimal level of cascara powder addition in producing Cascara crispy with the best chemical and sensory characteristics. This study used a completely randomized design with one factor and three replications. The treatments used were variations in the concentration of cascara powder at 0%, 2%, 4%, 6%, 8%, and 10%. The parameters analyzed included chemical characteristics (crude fiber content, total phenols, antioxidant activity, and caffeine content) and sensory characteristics (hedonic test and scoring test). The data were then analyzed using ANOVA and Duncan’s multiple range test. The results of the study showed that the best treatment was obtained with the addition of 10% cascara powder with a crude fiber content of 9.14%, total phenols of 25.61 mg GAE/100 g, antioxidant activity of 73.68%, and caffeine content of 0.26%. The product had a dark brown color, crispy texture, and slightly bitter taste, with color, aroma, and texture preferred by the panelists. In conclusion, the addition of up to 10% cascara powder produced Cascara crispy with the best characteristics and has potential as a basis for the development of functional food products.